CITY AS A TEXT IN THE CONTEMPORARY UKRAINIAN LITERATURE - Kohut О. V.; Maliarchuk О. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The paper is devoted to the analysis of city as a text in the novel of S. Horban and T. Lapina “The love affair with the city” The researchers consider urban loci as a means of identification of homo leopolensis esse and trace transformation of urban loci depending on changes of social and political life of Lviv and its inhabitants who have become an integral part of the city.